Catalyst for removing nitrogen oxides and method for producing same

A vanadium-zeolite catalyst with a carbon-coated surface and mechanical grinding enhances sulfur resistance and maintains catalytic activity by trapping ammonium bisulfate, addressing deactivation issues in V-based SCR catalysts.

JP7659278B2Active Publication Date: 2025-04-09SEOUL NATIONAL UNIVERSITY R&DB FOUNDATION +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023102919
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-11-08
Filing Date
2023-06-23
Publication Date
2025-04-09
Estimated Expiration
2043-06-23

AI Technical Summary

Technical Problem

Existing V-based SCR catalysts for nitrogen oxide removal are deactivated at low temperatures due to physical poisoning by ammonium bisulfate (ABS) condensation, leading to reduced activity and sulfur resistance.

Method used

A catalyst is prepared by mixing a metal catalyst, specifically vanadium (V), with a zeolite having a carbon layer formed on its surface, and grinding the mixture to enhance sulfur resistance and prevent deactivation.

Benefits of technology

The catalyst maintains excellent catalytic activity and sulfur resistance by effectively trapping ammonium bisulfate, preventing deactivation even under low-temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659278000002
    Figure 0007659278000002
  • Figure 0007659278000003
    Figure 0007659278000003
  • Figure 0007659278000004
    Figure 0007659278000004
Patent Text Reader

Abstract

To provide a nitrogen oxide removal catalyst and a producing method thereof.SOLUTION: A nitrogen oxide removal catalyst according to the embodiment of the present invention is produced by mixing a metal catalyst and a zeolite, and then grinding the mixture, and the zeolite has a carbon layer formed on its surface. A method for producing the nitrogen oxide removal catalyst according to the embodiment of the present invention includes the steps of forming the carbon layer on a zeolite surface, and mixing the zeolite with the carbon layer formed thereon with a metal catalyst, and then grinding the mixture.SELECTED DRAWING: Figure 11
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for removing nitrogen oxides and a method for producing the same. [Background technology]

[0002] Selective catalytic reduction of nitrogen oxides (NOx) using NH3 (NH3-SCR) is a technology for removing harmful NOx species from industrial emissions. Among SCR catalysts, V2O5-WO3 / TiO2 is the only catalyst that is not chemically poisoned by the sulfur components of exhaust gas. However, even such V-based catalysts are deactivated under practical conditions at low temperatures below 250°C due to physical poisoning caused by condensation of ammonium disulfate (ABS) in the pores, reducing the low-temperature activity of the SCR catalyst. Summary of the Invention [Problem to be solved by the invention]

[0003] The present invention provides a catalyst for removing nitrogen oxides having excellent performance. The present invention provides a method for producing the nitrogen oxide removing catalyst. Other objects of the present invention will become apparent from the following detailed description and the accompanying drawings. [Means for solving the problem]

[0004] The catalyst for removing nitrogen oxides according to the embodiment of the present invention is prepared by mixing a metal catalyst and a zeolite and grinding the mixture. The zeolite has a carbon layer formed on its surface.

[0005] A method for manufacturing a catalyst for removing nitrogen oxides according to an embodiment of the present invention includes forming a carbon layer on a surface of zeolite, mixing the zeolite with the carbon layer formed thereon with a metal catalyst, and grinding the resulting mixture. Effect of the Invention

[0006] The catalyst for removing nitrogen oxides according to the embodiment of the present invention may have excellent performance. For example, the catalyst for removing nitrogen oxides may have excellent sulfur resistance (SO2 resistance) while preventing a decrease in catalytic activity (SCR activity). [Brief description of the drawings]

[0007] [Figure 1] Figure 2 shows the NH3-SCR activity at 220 °C of VWTi and VWTi+Y catalysts deactivated by ABS formation for 22 h. [Diagram 2] 4 shows the steady-state NOx conversion of VWTi and VWTi+Y catalysts as a function of temperature during a standard NH3-SCR reaction. [Diagram 3] 1 shows the effect of the mass ratio of VWTi to Y zeolite in the VWTi+Y catalyst on the catalytic activity. [Figure 4] Solid-state 29Si NMR spectra of the VWTi+Y-5.1 catalyst without and with mechanical grinding are shown. [Diagram 5] Figure 1 shows the solid-state 27Al NMR spectra of the VWTi+Y-5.1 catalyst without and with mechanical grinding. [Figure 6] Figure 1 shows the solid-state 51V NMR spectra of the VWTi+Y-5.1 catalyst without and with mechanical grinding. [Figure 7] TEM images and EDS line scan spectra of VWTi+Y-12 and VWTi+Y-5.1 catalysts after grinding are shown. [Figure 8] 1 shows H2-TPR results comparing the effect of mechanical grinding on VWTi+Y-5.1 and VWTi+Y-12 catalysts. [Figure 9] The H2-TPR results of the Al-impregnated VWTi catalyst are shown. [Figure 10] The results of kinetic analysis of VWTi and VWTi+Y-5.1 catalysts under dry and wet reaction conditions are presented. [Figure 11] 1 is a diagram illustrating a method for producing a nitrogen oxide removing catalyst according to an embodiment of the present invention. [Figure 12] 51V solid-state NMR spectra of the VWTi catalyst and the VWTi+OTSY-5.1 catalyst. [Figure 13] The H2-TPR results for the VWTi catalyst and the VWTi+OTSY-5.1 catalyst are shown. [Figure 14] 4 shows steady-state NOx conversion as a function of temperature during a standard NH3-SCR reaction for the VWTi+OTSY-5.1 catalyst and the calcined form of this catalyst (VWTi+SY-5.1). [Figure 15] The catalyst was subjected to ABS formation and the NOx conversion rate in the NH3-SCR reaction at 220°C during 44-hour inactivation was shown. [Figure 16] ABS was formed on the VWTi catalyst and the VWTi+OTSY-5.1 catalyst, and NOx conversion in the NH3-SCR reaction at 180°C during 44 h deactivation was shown. BEST MODE FOR CARRYING OUT THEINVENTION

[0008] The present invention will be described in detail below with reference to the following examples. The objects, features, and advantages of the present invention will be readily understood from the following examples. The present invention is not limited to the embodiments described herein, and may be embodied in other forms. The embodiments described herein are provided so that the disclosed content will be thorough and complete, and will fully convey the concept of the present invention to those skilled in the art to which the present invention pertains. Therefore, the present invention should not be limited by the following examples.

[0009] In the drawings, the size of elements or the relative size between elements may be somewhat exaggerated for a clearer understanding of the present invention. In addition, the shapes of the illustrated elements may be somewhat changed due to variations in the manufacturing process, etc. Therefore, unless otherwise specified, the embodiments disclosed in this specification should not be limited to the shapes illustrated, and should be understood to include some modifications.

[0010] The catalyst for removing nitrogen oxides according to the embodiment of the present invention is manufactured by mixing a metal catalyst and a zeolite and then grinding the mixture. The zeolite has a carbon layer formed on its surface. The metal catalyst comprises vanadium (V) and the zeolite comprises a Y zeolite. The carbon layer is formed by reacting an organosilane compound with hydroxyl groups on the surface of the zeolite, the organosilane compound comprising octadecyltrichlorosilane. A method for manufacturing a catalyst for removing nitrogen oxides according to an embodiment of the present invention includes forming a carbon layer on a surface of zeolite, mixing the zeolite with the carbon layer formed thereon with a metal catalyst, and grinding the resulting mixture. The metal catalyst comprises vanadium (V) and the zeolite comprises a Y zeolite. The step of forming the carbon layer includes providing an organosilane compound to the zeolite, the organosilane compound reacting with hydroxyl groups on the surface of the zeolite, the organosilane compound including octadecyltrichlorosilane.

[0011] [Example of manufacturing catalyst for removing nitrogen oxides] The catalyst for removing nitrogen oxides according to the examples of the present invention and the catalyst for comparison were produced by the following method.

[0012] The V2O5 / WO3-T12 catalyst (VWTi catalyst) containing 5 wt.% V2O5 can be produced by wet impregnation method. Prepare an acidic vanadium precursor solution by dissolving 0.647 g of ammonium metavanadate (99%) and 0.6 g of oxalic acid in 250 mL of distilled water. Add the WO3-TiO2 support to the vanadium precursor solution and mix vigorously for 30 min. The yellow colloidal solution is dried using a rotary evaporator at 80 °C and in an oven at 105 °C. The resulting powder is calcined in an electronic furnace at 500 °C for 4 h.

[0013] The VWTi+Y zeolite hybrid catalysts are prepared by grinding and mixing VWTi catalyst and Y zeolite (FAU structure, Si:Al2=5.1 or 12) in a ceramic mortar for 10 min, with the mass ratios of VWTi to Y zeolite being 2:1, 16:1, and 64:1.

[0014] The required amount of Al(NO3)3·9H2O to prepare Al-VWTi catalyst is dissolved in distilled water and then deposited on the VWTi catalyst using the incipient wetness impregnation method. The molar ratios of Al to V are 0.5, 1, and 2. After impregnation, the samples are calcined in static air at 500 °C for 1 h.

[0015] To prepare octadecyltrichlorosilane (OTS)-coated Y zeolite (OTSY), firstly disperse Y-5.1 zeolite (1 g, Si:Al2=5.1) in 20 mL of toluene and sonicate for 10 min. Dissolve 0.591 mL of octadecyltrichlorosilane (OTS) in 50 mL of toluene solvent. Add the dispersed Y-5.1 zeolite to the OTS-toluene solution and stir at 30 °C for 24 h. Filter the suspension with filter paper and wash with ethanol several times. Dry the resulting white powder in an oven at 105 °C overnight to form OTSY-5.1 zeolite.

[0016] Starch powder was used to prepare the hydrocarbon-modified Y zeolite composite used for comparison with OTSY-zeolite. 0.18 g starch and 1 mL NH4OH were added to distilled water (250 mL) and swollen at 90 °C for 4 h. 2.5 g Y zeolite was added and stirred for 1 h before drying using a rotary evaporator. The resulting composite (starch-Y) was dried overnight in an oven at 105 °C. Elemental analysis showed that the carbon content of OTSY-5.1 zeolite (2.8 wt.%) and starch-Y-5.1 (2.2 wt.%) was similar.

[0017] [Catalytic reaction system] The catalytic activity of various catalysts for the NH3-SCR reaction was measured in a 0.25-inch tubular quartz reactor. All catalysts were pelletized and sieved to 180-250 μm to prevent pressure drop and ensure data reproducibility. The simulated reaction feed contained N2 (remainder excluding other reaction feeds), NO (500 ppm), NH3 (600 ppm), O2 (10%), CO2 (5%), H2O (10%, deionized), and SO2 (30 or 100 ppm). The gas hourly space velocity (GHSV) of the reaction feed was 150,000 mL / h g cat The GHSV was set based on the weight of VWTi catalyst (0.08 g) for the mechanically mixed hybrid catalyst (0.08 g VWTi + 0.04 g Y-zeolite). The total flow rate was fixed at 200 mL / min. The NOx concentration was recorded using a NOx chemiluminescence analyzer, and the NOx conversion was calculated using the following equation:

[0018]

number

[0019] To simulate ABS deactivation in the presence of SO2 and H2O, the catalyst was exposed to 30 or 100 ppm SO2 at 180 or 220°C for 22 or 44 hours under the reaction conditions described above. Catalyst deactivation towards ABS formation increases with increasing SO2 concentration and decreasing reaction temperature. For decomposition of ABS species and regeneration of the catalyst, the catalyst was heated with 10% O2, 5% CO2, and 10% H2O balance in N2 at 350°C for 2 hours.

[0020] Figure 1 shows the NH3-SCR activity at 220 °C of VWTi and VWTi+Y catalysts deactivated by ABS formation for 22 h. The mass ratio of VWTi to Y zeolite in VWTi+Y catalyst is 2:1. A well-mixed catalyst is formed by mechanical mixing and grinding of VWTi catalyst and Y zeolite. Two different particles, namely zeolite and TiO2, can be easily distinguished due to their different sizes. Zeolite has a size of hundreds of nanometers, while TiO2 particles are very small, tens of nanometers. The reaction feed contains N2 (the rest except other reaction feeds), NO (500 ppm), NH3 (600 ppm), O2 (10%), CO2 (5%), H2O (10%), and SO2 (30 ppm). The GHSV of the reaction feed is 150,000 mL / g·h.

[0021] Referring to Figure 1, the VWTi catalyst shows catalytic activity deactivated at low temperature (220°C) in the presence of ABS. The initial NOx conversion was 65%, which gradually decreased to about 40% after 22 hours. The initial activity of the VWTi+Y catalyst, which was prepared by mixing VWTi with Y zeolite having a Si:Al2 ratio of about 12, was similar to that of the VWTi catalyst, but the ABS deactivation proceeded much slower due to the ABS trapping ability of the zeolite particles in the VWTi+Y catalyst.

[0022] The VWTi+Y catalyst, prepared by mixing Al-rich Y zeolite (Si:Al2 = ca. 5.1:1) with VWTi, exhibited a completely different behavior. Although the initial activity dropped significantly from 65% to 45%, this initial activity was maintained for 22 h without any decrease in NOx conversion. The excellent sulfur tolerance of the VWTi+Y catalyst indicates that the Al-rich zeolite can absorb ABS more efficiently on the VWTi surface compared with the general zeolite. The particle sizes of Y-5.1 zeolite (Si:Al2 = ca. 5.1:1) and Y-12 zeolite (Si:Al2 = ca. 12:1) are almost the same, which means there is no difference in the physical contact area between the zeolite and the VWTi particles. Therefore, the only difference between Y-5.1 zeolite and Y-12 zeolite is the acidic sites of Al species that promote the migration of ABS.

[0023] Figure 2 shows the steady-state NOx conversion of VWTi and VWTi+Y catalysts as a function of temperature during a standard NH3-SCR reaction. The steady-state activity of the catalysts was compared over a wide temperature range to identify the cause of the initial activity drop of the VWTi+Y-5.1 catalyst. Figure 3 shows the effect of the mass ratio of VWTi to Y zeolite on the catalytic activity in the VWTi+Y catalyst. The mixture ratio of VWTi to Y zeolite was varied to determine whether the catalyst deactivation due to grinding was due to the Al-rich zeolite. The reaction feed contained N2 (the remainder excluding other reaction feeds), NO (500 ppm), NH3 (600 ppm), O2 (10%), CO2 (5%), and H2O (10%), and the GHSV of the reaction feed was 150,000 mL / g·h.

[0024] Referring to Figure 2, mechanical mixing of Y-5.1 zeolite caused a slight decrease in the activity of the VWTi catalyst over the entire temperature range (150-350 °C), while mixing of Y-12 zeolite had little effect on the SCR performance.

[0025] Referring to Figure 3, in the case of VWTi+Y-12 catalyst, the initial catalytic activity was slightly decreased at a mass ratio of 64:1, but the initial catalytic activity was maintained to some extent regardless of the mixing ratio of VWTi to Y-zeolite. However, as more Y-5.1 zeolite was added, the NOx conversion rate gradually decreased and the SO2 resistance constantly increased. The amount of Al-rich Y-zeolite mixed with VWTi had a significant effect on the catalytic activity and ABS trapping ability at the same time, and the Al species in the zeolite appeared to be the cause of the decrease in initial catalytic activity while providing sulfur resistance.

[0026] Figures 4 to 6 show the solid state of the VWTi+Y-5.1 catalyst without grinding and with mechanical grinding, respectively. 29 Si, 27 Al, and 51V NMR spectra are shown. The mass ratio of VWTi to Y-5.1 zeolite was 2:1, and the unground VWTi+Y-5.1 catalyst was prepared by gently mixing the two materials from a glass bottle with a hand shake. To investigate the cause of the abnormal catalyst deactivation after physical mixing, the Al-rich Y-5.1 and VWTi were ground, and then the physicochemical changes of the materials were analyzed by various characterization methods.

[0027] Referring to Figs. 4 to 6, 29 The Si-NMR spectrum showed a decrease in the peak intensity at -107 ppm, which corresponds to a tetrahedral coordination structure of the Si-O group, while the increase in the peaks at chemical shifts of -90 and -95 ppm is due to the Si-O group surrounded by three or two Al. 27 The Al-NMR spectrum shows Al in the extra-framework Al (0 ppm). VI and the increase in the peak corresponding to extra-framework Al (EFAl). V The catalyst shows a slight decrease in the intensity of the peaks, indicating a decrease in 4-coordinated EFAl and an increase in 6-coordinated EFAl species. This change means that some EFAl species can be switched again to framework Al species during grinding even under ambient conditions, indicating that applying mechanical force to the catalyst can induce the structural rearrangement of framework Al or the migration of EFAl species in the zeolite cage.

[0028] Mechanical grinding had a significant effect on the coordination environment of not only Al species but also V species. The peaks of highly dispersed and isolated monomeric VOx species (-535 and -572 ppm) on the TiO2 surface almost disappeared after grinding, and only the peak at -614 ppm corresponding to oligomeric VOx or nano-sized V2O5 remained after grinding. Observing the simultaneous decrease of dispersed VOx species and the change of Al species in the zeolite structure, it can be confirmed that mechanical grinding induces the interaction between V and Al species, which is due to the diffusion of mobile Al species from the TiO2 surface to the isolated VOx species. Also, the amount of NH3 desorption at low temperatures decreased after grinding, whereas the number of acidic sites increased at high temperatures.

[0029] Figure 7 shows the TEM images and EDS line scan spectra of the VWTi+Y-12 and VWTi+Y-5.1 catalysts after grinding. The mass ratio of VWTi to Y zeolite is 2:1.

[0030] With reference to FIG. 7, some of the VWTi particles contained significant amounts of Al after mechanical mixing, indicating possible EFAl migration and subsequent interaction with isolated V sites as a result of the grinding process.

[0031] FIG. 8 shows the H2-TPR results comparing the mechanical grinding effect for the VWTi+Y-5.1 and VWTi+Y-12 catalysts, and FIG. 9 shows the H2-TPR results for the Al-impregnated VWTi catalyst.

[0032] With reference to Figure 8, the change in Al species due to mechanical interactions in the VWTi+Y-5.1 catalyst led to changes in the redox behavior of isolated V sites. The full reduction peak of 370-620 °C, assigned to the reduction of dispersed VOx and WOx species in the H2-TPR profile, moved to higher temperatures after grinding. The use of Y-5.1 zeolite led to a more distinct change in the reduction temperature of the mixed catalyst compared to Y-12 zeolite. The significant change in the reducibility of isolated VOx species can only be explained by their chemical interaction with Al species, which inhibits the reduction of VO-Ti by forming Al-O bonds.

[0033] Referring to Figure 9, in order to confirm the potential effect of Al species on the reducibility of VOx, the VWTi catalyst was impregnated with Al(NO3)3 solution to simulate the migration of Al, and the change in the H2-TPR results was observed. A similar trend was observed in the Al-impregnated VWTi catalyst, where the reduction peaks below 450 °C decreased, but the peaks above 500 °C increased as Al was impregnated. These results indicate that the diffused Al species derived from zeolite affect the reducibility of VOx species against TiO2 through the grinding process.

[0034] Figure 10 shows the results of kinetic analysis of VWTi and VWTi+Y-5.1 catalysts under dry and wet reaction conditions. To investigate the effect of VOx-Al interaction on the reaction pathway in the SCR reaction, the catalytic kinetic analysis was performed. The mass ratio of VWTi to Y-5.1 zeolite in the VWTi+Y-5.1 catalyst is 2:1.

[0035] Referring to Figure 10, the activation energy (Ea) of the VWTi catalyst with wet feed was measured to be about 60 kJ / mol under standard SCR conditions. However, after grinding with Y-5.1 zeolite, the activation energy increased to about 69 kJ / mol. Similarly, the activation energy of VWTi under dry conditions was 52 kJ / mol, while the activation energy of the VWTi+Y-5.1 catalyst increased to 64 kJ / mol, indicating an increase in activation energy with or without water. The change in reaction dynamics represented by the increase in activation energy can only be explained by the modulation of the active sites of the reaction.

[0036] The activation energy of the Al-impregnated VWTi catalyst was higher than that of the VWTi catalyst (72 kJ / mol), as was the VWTi+Y-5.1 catalyst. Thus, the interaction between V and Al causes a higher activation energy in the SCR reaction, which is the main cause of catalyst deactivation after grinding. The surface VOx species of TiO2 are dynamic under reaction conditions, which means that changes in VOx dispersion can cause deactivation after grinding. To confirm this, kinetic analysis of VWTi catalysts with various V loadings was performed under wet conditions, which showed that the activation energy was 52–60 kJ / mol regardless of V loading. Thus, the increase in activation energy of the VWTi+Y-5.1 catalyst is attributed to interactions with Al species rather than changes in V dispersion.

[0037] FIG. 11 is a diagram for explaining a method for producing a nitrogen oxide removing catalyst according to one embodiment of the present invention.

[0038] Referring to Fig. 11, before mixing VWTi and Y zeolite, Y zeolite is coated with a carbon layer. Octadecyltrichlorosilane (OTS) is dissolved in a toluene solvent to form an OTS-toluene solution, and Y zeolite is added to the OTS-toluene solution. OTS reacts with the hydroxyl groups of Y zeolite to form HCl, and Y zeolite is coated with OTS to form an OTS layer (carbon layer) on the surface of Y zeolite. Y zeolite with an OTS layer (OTSY) is mixed with VWTi and then ground to produce VWTi+OTSY-5.1 catalyst.

[0039] Figure 12 shows the results of the VWTi catalyst and the VWTi+OTSY-5.1 catalyst. 51 V shows the solid-state NMR spectra, and Fig. 13 shows the H2-TPR results of the VWTi catalyst and the VWTi+OTSY-5.1 catalyst.

[0040] Referring to Figures 12 and 13, the VWTi+OTSY-5.1 catalyst coated with a carbon layer had similar results before and after grinding. 51 V NMR peak intensity was observed. Also, the H2-TPR profile did not show any decrease in the reducibility of VWTi after grinding. These results indicate that isolated VOx is preserved without interaction with Al species.

[0041] Figure 14 shows the steady-state NOx conversion as a function of temperature during a standard NH3-SCR reaction for the VWTi+OTSY-5.1 catalyst and the calcined form of this catalyst (VWTi+SY-5.1). The mass ratio of VWTi to OTSY-5.1 zeolite in the VWTi+OTSY-5.1 catalyst is 2:1.

[0042] Referring to Figure 14, compared with the VWTi+Y-5.1 catalyst, the VWTi+OTSY-5.1 catalyst maintained its initial catalytic activity without deactivation from 100 to 300 °C. This indicates that the thin carbon layer on the outer surface of the zeolite particles effectively acts as a physical barrier and protects the isolated active VOx sites on the TiO2 surface by preventing the diffusion of Al species. After the SCR reaction was performed on this catalyst up to 500 °C, the reactor was cooled to room temperature and retested under the same conditions. In the secondary SCR test, there must be direct contact between the VWTi and the zeolite particles because most of the carbon layer is removed by oxidation. Elemental analysis of the OTSY-5.1 catalyst showed that only a small amount of the carbon layer remained after oxidation at 500 °C. Despite the direct contact between the zeolite and the VWTi particles, the SCR activity was fully maintained without any changes in the secondary SCR test, indicating that no chemical deactivation by mobile EFAl species occurs without the mechanical grinding step. This means that the migration of Al species (mostly EFAl) to neighboring particles occurs due to mechanical forces and not due to differences in chemical potential. For comparison, carbon-coated OTSY-5.1 was pre-oxidized at 500 °C to produce SY-5.1, and VWTi+SY-5.1 catalyst was also produced to observe what would happen if the carbon layer was removed before grinding. In this case, as expected, a decrease in SCR activity was observed again, similar to that observed for VWTi+Y-5.1. This indicates that the silane groups remaining on the zeolite after oxidation cannot prevent the mechanical and chemical interaction between VOx and Al species. That is, a thin carbon layer must be present on the zeolite surface that prevents direct contact of V with the zeolite during the grinding process.

[0043] FIG. 15 shows the NOx conversion in NH3-SCR reaction at 220°C after ABS formation on the catalyst and deactivation for 44 hours. The catalyst was regenerated at 350°C for 2 hours between 22 and 24 hours of operation. The reaction feed contained N2 (the remainder excluding other reaction feeds), NO (500 ppm), NH3 (600 ppm), O2 (10%), CO2 (5%), H2O (10%), and SO2 (100 ppm), and the GHSV of the reaction feed was 150,000 mL / g·h. FIG. 16 shows the NOx conversion in NH3-SCR reaction at 180°C after ABS formation on the VWTi catalyst and VWTi+OTSY-5.1 catalyst and deactivation for 44 hours. To monitor the deactivation process, the catalyst was heated to 220°C after 22 and 48 hours. The mass ratio of VWTi to zeolite in the VWTi+zeolite catalyst is 2:1.

[0044] Referring to Figure 15, the VWTi+OTSY-5.1 catalyst successfully maintained high SO2 resistance without physical deactivation by ABS during 44 hours of operation while maintaining initial catalytic activity without chemical deactivation occurring with EFAl species. This performance is superior to that of traditional VWTi and Mn-based catalysts and can be utilized in combustion facilities with sulfur-containing exhaust gases.

[0045] Referring to FIG. 16, low temperatures (below 200°C) can further accelerate the deactivation of ABS, because the vapor pressure of ABS decreases significantly as the temperature decreases. Therefore, the catalyst was also tested at a much lower temperature (180°C), where condensation of ABS in the catalyst pores occurred more easily. The conventional VWTi catalyst lost activity rapidly in 5 hours under these conditions, and the activity was still low (less than 20%) when the temperature was increased to 220°C, because the condensed ABS is not easily decomposed at this temperature. In contrast, the VWTi+OTSY-5.1 catalyst maintained activity with almost no deactivation for 22 hours, and the activity was still high (about 60%) when the temperature was restored to 220°C. It was also confirmed that the catalyst was not completely deactivated even when exposed to lower temperatures for 44 hours, indicating that low temperature events occurring during actual SCR operation can be prevented.

[0046] Instead of using silanes to see if bulk carbon would have a similar effect to the thin carbon layers produced with organosilanes, a bulk carbon compound, colloidal starch, was deposited in aqueous solution on zeolite particles and mixed with the VWTi catalyst. In this case, ABS deactivation occurred. This is because, unlike the OTS layer, which only covers the outer surface of the zeolite, the long colloidal starch ligands induce zeolite aggregation and inhibit sufficient VWTi-zeolite contact for ABS trapping. This indicates that the carbon layer should be introduced in a way that does not interfere with the essential contact between the VWTi and the zeolite for efficient ABS trapping.

[0047] Specific examples of the present invention have been discussed above. Those skilled in the art will understand that the present invention can be embodied in modified forms without departing from the essential characteristics of the present invention. Therefore, the disclosed embodiments should be considered in an illustrative rather than restrictive sense. The scope of the present invention is defined in the claims, not in the above description, and all differences within the scope of the claims should be interpreted as being included in the present invention.

Claims

[Claim 1] forming a carbon layer on the zeolite surface; and The zeolite having the carbon layer formed thereon is mixed with a metal catalyst and then ground; The metal catalyst comprises vanadium (V); The zeolite comprises a Y zeolite; forming the carbon layer includes providing an organosilane compound to the zeolite; The organosilane compound reacts with hydroxyl groups on the surface of the zeolite, The method for producing a catalyst for removing nitrogen oxides, wherein the organosilane compound contains octadecyltrichlorosilane.

Citation Information

Patent Citations

  • Catalyst for purifying exhaust gas

    JP1991135437A

  • Method for removing nitrogen oxides in waste combustion gas

    JP1991181321A

  • Method for protecting solid adsorbents, and protected solid adsorbents

    JP2013523424A

  • SCR catalyst with excellent sulfur resistance

    JP2022531806A